In-Line Filtration Reduces Postoperative Venous Peripheral Phlebitis Associated With Cannulation: A Randomized Clinical Trial. (December 2018) - Villa, Gianluca; Chelazzi, Cosimo; Giua, Rosa; Tofani, Lorenzo; Zagli, Giovanni; Boninsegni, Paolo; Pinelli, Fulvio; De Gaudio, A. Raffaele; Romagnoli, Stefano
Abstract : BACKGROUND: Peripheral venous cannulation is an everyday practice of care for patients undergoing anesthesia and surgery. Particles infused with intravenous fluids (eg, plastic/glass/drugs particulate) contribute to the pathogenesis of peripheral phlebitis. The aim of this study is to demonstrate the efficacy of in-line filtration in reducing the incidence of postoperative phlebitis associated with peripheral short-term vascular access. METHODS: In this controlled trial, 268 surgical patients were randomly assigned to in-line filtration and standard care (NCT03193827). The incidence of phlebitis (defined as visual infusion phlebitis [VIP] score, ≥2) within 48 hours was compared between the 2 groups, as well as the onset and severity of phlebitis and the reasons for removal of the cannula. The lifespan of venous cannulae was compared for the in-line filter and no-filter groups through a Kaplan-Meier curve. RESULTS: The incidence of phlebitis within 48 hours postoperatively was 2.2% and 26.9% (difference, 25% [95% confidence interval CI, 12%–36%]; odds ratio, 0.05 [0.01–0.15]), respectively, for the in-line filter and no-filter groups ( P < .001). From 24 to 96 hours postoperatively, patients in the no-filter group had higher VIP scores than those in in-line filter group ( P < .001). Venous cannulae in the in-line filter group exhibited prolonged lifespan compared to those in the no-filter group ( P = .01). In particular, 64 (47.8%) of cannulae in the in-line filter group and 56 (41.8%) of those in the no-filter group were still in place at 96 hours postoperatively. At the same time point, patients with a VIP score <3 were 100% in the in-line filter group and only 50% for the no-filter group. In-line filtration was a protective factor for postoperative phlebitis (hazard ratio, 0.05 [95% CI, 0.014–0.15]; P < .0001) and cannula removal (hazard ratio, 0.7 [95% CI, 0.52–0.96]; P = .02). CONCLUSIONS: In-line filtration has a protective effect for postoperative phlebitis and prolongs cannula lifespan during peripheral venous cannulation in surgical patients.